Design WAP-Based Co-Curriculum Course Registration System For Pusat Kokurikulum, UUM - Elgatait, Hussam-Eddin Alfitouri (2008)
The mobile devices & the emergence of wireless technology are rapidly increasing. This study identified and designed a WAP-based Co-curriculum Course Registration System (WCCRS) using WAPtor, MySQL and ASP. The WCCRS is a real-time application system capable of hassle free of co-curriculum course registration system. It provides a convenient graphics user interface (GUI) for both students and Pusat Ko-k administrators. It allows students to make self-registration for their selected co-curriculum, view timetable. Is also allows administrator to add/ delete student account, add/drop course, offer course and add course catalog. All of the services will be possible anywhere at any time. A requirements model called-"WCCRS" was built based on the identified functionalities and further tested by potential users to evaluate acceptance of the proposed requirements model. The evaluation was performed based on questionnaire. The overall results showed that majority of respondents satisfied with WCCRS. Nevertheless, for the future enhancement, recommendations from participants have been taken into considerations.